Physical mesomechanics of a deformed solid as a multilevel system. II. Chessboard-like mesoeffect of the interface in heterogeneous media in external fields; Physical Mesomechanics; Vol. 10, iss. 1-2, Jan.-Apr. - Panin V. E. Viktor Evgenyevich (2007, 2007)
Based on the earlier investigations and analysis of data in the literature we have experimentally revealed and theoretically justified the mesoscopic effect of a chessboard-like distribution of normal and tangential stresses at the interface of dissimilar media in external fields. The mesoeffect arises at the conjugation of very different media independently of their aggregate state (solid-liquid-gas) and governs the development of nonlinear wave mass transfer processes of different type. We draw a conclusion about the crucial role of the found effect in numerous natural phenomena, various areas of science and engineering